1992
DOI: 10.1143/jjap.31.3077
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Motors Using Longitudinal and Bending Multimode Vibrators with Mode Coupling by Externally Additional Asymmetry or Internal Nonlinearity

Abstract: The present paper deals with some ultrasonic motors using longitudinal and bending multimode vibrators with their mode couplings caused by externally additional asymmetry or internal nonlinearity. A rectangular plate vibrator with two corners on one diagonal line cut to make its resonance modes couple with each other was used, along with a rectangular plate vibrator under the condition that two resonance frequencies are obtained, for example, as f L/f B=2.0, because internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…The motor steps recorded experimentally are shown in Figure 7.2-7.9. As seen from these graphs, the motor exhibits the typical stair case step of inchworm motor at low frequencies (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Hz). However, at frequencies above 45 Hz, slippage becomes apparent in the motor step profile.…”
Section: Experiments Verification and Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The motor steps recorded experimentally are shown in Figure 7.2-7.9. As seen from these graphs, the motor exhibits the typical stair case step of inchworm motor at low frequencies (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Hz). However, at frequencies above 45 Hz, slippage becomes apparent in the motor step profile.…”
Section: Experiments Verification and Discussionmentioning
confidence: 86%
“…Control schemes have been devised to improve the response, speed and precision of these motors. Hatsuzawa et al (1986) and Aoyagi et al, (1992) have subjected the motor response with different input parameters such as frequency, voltage and phase [21,22]. Their studies have shown that for ultrasonic motor, speed is most sensitive to the operating frequency.…”
Section: Traveling Wave Ultrasonic Motors (Twum)mentioning
confidence: 99%
See 1 more Smart Citation
“…The motor's main feature was that it could rotate at higher speeds -4 -than motors previously developed under these conditions. Ultrasonic motors can generally be easily downsized due to their driving principles [9]- [13]. Some of these have been used in several specific environments [14]- [16].…”
Section: Introductionmentioning
confidence: 99%
“…These two designs are characterized mainly by their compactness. Since the 1980's, researchers in Japan carried out further research work on compact linear ultrasonic motors [5][6][7][8][9][10][11]. In literatures [8][9][10][11], many kinds of ultrasonic oscillators with multilayer piezoelectric actuators, which could lower the operating voltage and improve the lifetime of an ultrasonic linear motor, were reported.…”
Section: Introductionmentioning
confidence: 99%